Mengeksplorasi Potensi Kegiatan BUMDes Bagi Peningkatan Pendapatan Masyarakat Desa Labuhan Aji Kecamatan Tarano Kabupaten Sumbawa - Purwadinata, Subhan; Ferdaus, Nadia Nuril (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study aims to explore the potential of Village-Owned Enterprises (BUMDes) activities in increasing the income of the community in Labuhan Aji Village, Tarano Subdistrict, Sumbawa Regency. The focus of this research is to identify the types of activities carried out by BUMDes, their contribution to community welfare, and the challenges faced in managing village enterprises. The study employs a qualitative approach with a descriptive method, using in-depth interviews with BUMDes management, village officials, and community members involved in village economic activities. The findings indicate that BUMDes in Labuhan Aji Village operates several promising business units, including culinary businesses, service provision, and local product trading, which contribute positively to increasing community income. However, the development of BUMDes still faces obstacles such as limited capital, suboptimal business management, and uneven product promotion. This study concludes that optimizing the role of BUMDes through improved managerial capacity, financial support, and effective marketing strategies can be key to enhancing the welfare of the village community.